APPLICATION OF PATREC MODELING TO WILD TURKEY MANAGEMENT IN MISSOURI1 - Eric W. Kurzejeski; John B. Lewis (Wildlife Society Bulletin)
Abstract: The ability to quantify the effects of habitat manipulation on wild turkey populations is imperative in developing management programs. Predictive PATREC models for eastern wild turkeys (Meleagris gallopavo silvestris) are being constructed in Missouri to assess the impact of management options on turkey density. Two models were developed for wild turkeys in the mixed timber/agriculture regions of north Missouri, and the heavily timbered south‐central Ozarks. Model parameters for north Missouri were derived from 3 years of habitat use data collected with the use of radio telemetry. The south Missouri model was based on inventory data from the Mark Twain National Forest records. The models provide a structured approach to selecting management options based on their respective impact on turkey population densities which could be adopted to other habitat types. The utility of modeling as means of prioritizing release sites and assessing potential densities is discussed.